An integrated approach for extraction of lithology information using the SPOT 6 imagery in a heavily Quaternary‐covered region—North Baoji District of China. (20th November 2017) - Han, Ling; Zhao, Bo; Wu, Jian‐Jian; Zhang, Shu‐Yuan; Pilz, Jürgen; Yang, Fan
Abstract : We studied the applicability of SPOT (Systeme Probatoire d'Observation de la Terre) 6 satellite imagery for red sandstone interpretation in the heavily loess‐covered northern Baoji District, China, which is always a crucial but challenging issue in remote sensing geological mapping. First, the non‐ or sparsely vegetated subareas were outlined in order to narrow the interpretation target area; second, band‐math and the fractal "DN‐N" (digital number‐frequency) algorithm was conducted to extract the sandstone‐associated anomalies; third, a series of spatial analysis, for example, overlaying and clumping, was employed for elimination of the false anomalies; finally, we took advantage of matched filtering to discern the non‐ (red) sandstone outcrops in local areas. Generally, the interpretation accuracy based on this novel technical proposal is acceptable—74% or slightly less (taking the geological sketch as reference criteria)—and can be well proven by field investigation. This study may have contributed a useful case study for remote‐sensing lithological mapping in the Quaternary‐covered areas.